25. UTILIZATION OF TRADITIONAL MEDICINE METHODS IN THE CLINICAL TREATMENT OF RHINOSINUSITIS: A CROSS-SECTIONAL STUDY (Vietnam Journal of Community Medicine, 2025)
Objective: This study aimed to investigate traditional medicine methods in the clinical treatment of rhinosinusitis.Subjects and methods: A cross-sectional descriptive study through retrospective data analysis was conducted on medical record to examine traditional medicine treatment methods applied to outpatients with rhinosinusitis at the University Medical Center Ho Chi Minh city, campus 3 and the Traditional Medicine Hospital of Ho Chi Minh city, during the period from January 1 to December 31, 2024.Results: The prevalence of rhinosinusitis in females was 1.7 times higher than in males. Most patients were diagnosed with chronic rhinosinusitis (91.4%). The median age was 37.0 years (IQR: 30.3-46.0). The age group with the highest prevalence was 31-40 years (34.6%). A total of 96.4% of rhinosinusitis patients received herbal medicine. Among these, 87% were treated with finished herbal products, and 14.6% with herbal decoction. Non-pharmacological methods were used in 48.2% of patients, with thread-embedding acupuncture being the most common (33.3%).Conclusion: The traditional medicine methods used for rhinosinusitis mainly included finished herbal products and non-pharmacological methods.
Keywords: Rhinosinusitis, traditional medicine, herbal decoction, finished herbal product, non-pharmacological method.